Pengeringan Sari Buah Mengkudu (Morinda citrifolia L.) secara Spray Drying - Sri Ningsih; Siti Kadarsih; Wahono Sumaryono (JURNAL ILMU KEFARMASIAN INDONESIA, 2004)
Drying process of Mengkudu (Morinda citrifolia L.) juice by spray drying method had been carried out. Two kinds of fillers were used in this process, i.e. 5%, 15%, 20%, and 25% of lactose monohydrate or 15% and 20% of maltodextrin, both in w/w %. The result obtained showed, that the dried powder containing 15 % of maltodextrin was better (dry fine and brown) than those with other concentration of fillers.